2021
DOI: 10.3390/ma14247503
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon and Fundamental Properties of Eco-Efficient Mortar with Recycled Powders

Abstract: Using recycled powders from solid waste is accepted as an effective strategy to realize the sustainable development of the construction industry. In our study, the cement was substituted by two kinds of recycled powders, i.e., spontaneous combustion gangue powder (SCGP) and recycled concrete powder (RCP), with a certain replacement ratio of 30%. The experimental variables were mainly the type of replacement powder (e.g., SCGP, RCP, and SCGP + RCP) and the grinding time of RCP (e.g., 25 min, 50 min, and 75 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…One of the approaches is the deployment of environmentally friendly materials in the development of agro-industrial waste-based cement composites. Over the years, the environmental benefits of using agricultural and industrial by-products as SCMs have been extensively researched [63][64][65][66], resulting in lower global warming potential and greenhouse gas emissions, the preservation of natural resources and waste reduction.…”
Section: Environmental Impactmentioning
confidence: 99%
“…One of the approaches is the deployment of environmentally friendly materials in the development of agro-industrial waste-based cement composites. Over the years, the environmental benefits of using agricultural and industrial by-products as SCMs have been extensively researched [63][64][65][66], resulting in lower global warming potential and greenhouse gas emissions, the preservation of natural resources and waste reduction.…”
Section: Environmental Impactmentioning
confidence: 99%
“…However, due to the heterogeneity of the material, more research is needed comparing different origins and sources of the RCP. On the other hand, the environmental benefit of the use of RCP to reduce both the emission of carbon dioxide (CO 2 ) and the consumption of energy has been verified in the literature (31)(32)(33). He et al (32) indicated that up to a 20% RCP could reduce up to 17.5% of CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Cement production is one of the main causes of environmental problems due to the high consumption of energy and non-renewable mineral resources, and high carbon dioxide emission [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In order to promote the sustainable development of the cement industry, effective measures to reduce the consumption of energy and non-renewable mineral resources have become an important topic in the field of cement research.…”
Section: Introductionmentioning
confidence: 99%